2023
DOI: 10.3390/jcs7030111
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Experimental Analysis of Bricks Using Recycled Plastics and Bitumen

Abstract: Plastic is being used increasingly in daily life. Most of it is not recyclable, and the remaining plastic cannot be used or decomposed. This causes increased plastic waste, contributing to global warming due to thermal recycling. The major objective of this research was to utilise the maximum plastic waste possible to manufacture bricks that compete with the properties of conventional bricks without affecting the environment and the ecological balance. A balanced mixture of high-density polyethylene (HDPE), qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…• In the research led by Koppula [16], they obtained tests by adding plastic waste to make bricks without affecting the environment and ecological balance. They evaluated the quality of the bricks, such as compression tests, water absorption, and efflorescence.…”
Section: Evaluation Of the Physical And Mechanical Properties Of Brickmentioning
confidence: 99%
“…• In the research led by Koppula [16], they obtained tests by adding plastic waste to make bricks without affecting the environment and ecological balance. They evaluated the quality of the bricks, such as compression tests, water absorption, and efflorescence.…”
Section: Evaluation Of the Physical And Mechanical Properties Of Brickmentioning
confidence: 99%
“…These include the need for proper temperature control mechanisms to overcome the dangers associated with open flame usage 6,21,[29][30][31] and the danger of manual mixing methods which is linked to inconsistent mixing and poor dispersion of the materials used. 6,21,29,31 Additionally, some limitations in the manufacturing of plastic sand bricks include the restriction to specific fillers such as fly ash, [32][33][34] river and quarry sand 20,[35][36][37][38] and additives such as bitumen 39 and talc. 40 Currently, there is a lack of available literature on the use of Kaolin Clay as an additive in plastic sand bricks and its widespread use in the construction industry.…”
Section: Introductionmentioning
confidence: 99%
“…The primary objective of this study was to determine if low-value waste plastics could be used effectively as a replacement for traditional materials in South African road construction. Koppula et al [20] use high-density polyethylene (HDPE), quartz sand, and bitumen to make bricks, and found that this combination led to an improvement in the strength of the bricks while reducing their weight. So, recycling plastic waste into construction material will help in economic, environmentally friendly, and sustainable construction [21][22][23].…”
Section: Introductionmentioning
confidence: 99%